Low-Cost Single Chamber MFC Integrated With Novel Lignin-Based Carbon Fiber Felt Bioanode for Treatment of Recalcitrant Azo Dye - Fatima, Masoom; Kiros, Yohannes; Farooq, Robina; Lindström, Rakel W. (Frontiers in Energy Research, 2021)
A flow through anaerobic microbial fuel cell (MFC) was designed and optimized for efficient treatment of recalcitrant textile wastewater. The membrane-less MFC was first time fabricated with a unique combination of electrodes, a novel bioanode of synthesized lignin-based electrospun carbon fiber supporting a biofilm of Geobacter sulfurreducens for acetate oxidation and an air-breathing cathode, consisting of a pyrolyzed macrocycle catalyst mixture on carbon bonded by polytetrafluoroethylene (PTFE). The effects of different organic loadings of acetate along with Acid Orange (AO5), operation time and ionic strength of auxiliary salts (conductivity enhancers) were investigated and responses in terms of polarization and degradation were studied. In addition, the decomposition of the organic species and the degradation of AO5 along with its metabolites and degraded products (2-aminobenzenesulfonic acid) were determined by chemical oxygen demand (COD) analysis, UV-Vis spectrophotometry and high-performance liquid chromatography (UV-HPLC) techniques. SEM and TEM images were also used to find out the biocompatibility of the microbes on lignin-based electrospun carbon felt anode and the morphology of the cathode. Reduction and breakage of the azo bond of AO5 occurs presumably as a side reaction, resulting in the formation of 2-aminobenzenesulfonic acid and unidentified aromatic amines. Maximum current density of anode 0.59 Am−2 and power density of 0.12 Wm−2 were obtained under optimized conditions. As a result, decolouration of AO5 and chemical oxygen demand (COD) removal efficiency was 81 and 58%, respectively. These results revealed that the low-cost MFC assembly can offer significant potential for anaerobic decolouration of recalcitrant textile wastewater.